SELL-SIDE AND BUY-SIDE PERFORMANCE WITH TARGET PRICE IN BRAZIL - Leite Colares, Fabio Renato; Galdi, Fernando Caio (Advances in Scientific and Applied Accounting, 2021)
Objective: The objective of this research is to investigate the performance of Brazilian buy-side and sell-side analysts in forecasting target prices. We investigate the existence of bias, accuracy and level of reaching target prices.. Method: To investigate performance we used average tests. We also used regressions in order to find elements that explained the differences in the forecast of the target prices. The sample consisted of Brazilian companies accompanied by such analysts during the years 2013 to 2018, target prices stipulated by buy-side analysts from a Brazilian institutional investor and the market consensus of sell-side analysts extracted from Bloomberg. Results: The results indicated the existence of a more optimistic bias on the part of buy-side analysts in all tests. When all the companies in the sample were used, there was a better accuracy and better level of reaching target prices by sell-side analysts. When only ADR issuing companies were used, there was no difference in the accuracy and level of reaching target prices, and the optimistic bias was reduced for both groups of analysts. Contributions: This work contributes to the literature by pointing out that divergences in the performance of buy-side and sell-side analysts are evident for companies with less and less rigid analyst coverage; confirms that the weak institutional environment contributes to less accurate pricing (target prices); and advances in the quality of the sample in relation to other works, by using the same companies and the same object of study (target price). This article points out, as a direction for further research, the investigation of target price differences in companies with little analyst coverage, lower market value and lower trading volume.